An Analysis on Eight Grade Mathematics Textbook of New Indonesian Curriculum (K-13) Based on Pisa’s Framework - Sarlita Murdaningsih; Budi Murtiyasa (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2016)
This study aims to analyze and describe the mathematics problems in the eighth grade mathematics textbook of new Indonesian curriculum (K-13) based on The Programme for International Student Assesment (PISA) frameworks. The object of this study was the the revised version textbooks of the eighth grade mathematics student’s book published by The Ministry of Education and Culture (Kemendikbud) in 2014. The framework of the analysis in this study was the PISA components consisting of process, content, and context with its categories. The research method was descriptive quantitative. The data was collected by observing the contents of the textbook and interviewing the students and the teachers in SMP Negeri 2 Rembang. The analysis showed that the contents of the textbook were in accordance to the PISA components. The result also indicated that in both semester of the students’ book, the problems involving the process of employing mathematical concepts, facts, procedures, and reasoning were more dominant than others. Moreover, in the contexts, the problems were dominated by the personal context. Furthermore, the first semester students’ books were dominated by the change and relationships contents while the second semester books were dominated by the space and shape contents.